Design Analysis And Modelling Of Autonomous Underwater Vehicle (AUV) Using CAD - Mohd Aras, Mohd Shahrieel; Khor, Li Zhe; Aripin, Muhamad Khairi; Tan, Pheng Chaing; Mohd Shah, Hairol Nizam; Khamis, Alias; Nordin, Nurdiana; Ab Rashid, Mohd Zamzuri (National Institute Of Science Communication And Information Resources (NISCAIR), 2019)
In the underwater world, an autonomous underwater vehicle (AUV) is created to assist in underwater research. This project presents a design analysis and modelling of AUV using computer aided design (CAD) simulation software, SolidWorks. The scope of this project divided into two parts: (a) AUV design and (b) analysis of battery enclosure stress and strain simulation and flow simulation of 3-blade propeller T100 thrusters. The AUV was designed part by part first and then the assembly of all the parts is carried out. In the simulation stress and fluids were applied on the enclosure box and a thruster, respectively, to observe the reaction of the parts as the frame and pressure hull from Blue ROV design. The result of the stress simulation shows that the enclosure box is very durable and can withstand up to 718.10 Pascal equivalents to 73.2 meter underwater depth. Furthermore, the outcome of flow simulation by using SolidWorks has shown that the maximum velocity of thruster flow is 4.939 m/s, while the acceleration of 5.655 m/s2 of the AUV is calculated by using thrust force and mass of the AUV.